Alkaline phosphatase and OCT‐3/4 as useful markers for predicting susceptibility of human deciduous teeth‐derived dental pulp cells to reprogramming factor‐induced iPS cells. Issue 4 (18th September 2016) - Inada, Emi; Saitoh, Issei; Kubota, Naoko; Soda, Miki; Matsueda, Kazunari; Murakami, Tomoya; Sawami, Tadashi; Kagoshima, Akiko; Yamasaki, Youichi; Sato, Masahiro
Abstract: Aim: The aim of the present study was to prove that primary cells enriched with stem cells are more easily reprogrammed to generate induced pluripotent stem (iPS) cells than those with scarce numbers of stem cells. Methods: We surveyed the alkaline phosphatase (ALP) activity in five primarily‐isolated human deciduous teeth‐derived dental pulp cells (HDDPC) with cytochemical staining to examine the possible presence of stem cells. Next, the expression of stemness‐specific factors, such as OCT(Octumer‐binding transcription factor)3/4, NANOG, SOX2(SRY (sex determining region Y)‐box 2), CD90, muscle segment homeodomain homeobox (MSX) 1, and MSX2, was assessed with a reverse transcription polymerase chain reaction method. Finally, these isolated HDDPC were transfected with plasmids carrying genes coding Yamanaka factors to determine whether these cells could be reprogrammed to generate iPS cells. Results: Of the five primarily‐isolated HDDPC, two (HDDPC‐1 and ‐5) exhibited higher degrees of ALP activity. OCT‐3/4 expression was also prominent in those two lines. Furthermore, these two lines proliferated faster than the other three lines. The transfection of HDDPC with Yamanaka factors resulted in the generation of iPS cells from HDDPC‐1 and ‐5. Conclusion: The number of cells with the stemness property of HDDPC differs among individuals, which suggests that HDDPC showing an increased expression of both ALP and OCT‐3/4 can be more easily reprogrammed to generate iPS cells after the forced expression of reprogramming factors.